The effect of anti-diabetic agents oil biochemical changes of diabetic rats - Gabr, Mahmoud M; Refaie, Ayman F (African Journal of Nephrology, 2023)
The present study was petformed to investigate the effect of vitamin E as an antioxidant and selenium as a potent insulin-mimetic agent in diabetic rats. Also, to study the ability of these treatments to ameliorate some of the biochemical changes that are worsened with the development of diabetes, such as; serum glucose, blood malondialdehyde (MDA), triglycerides, total cholesterol and β₂-microglobulin. Experimental diabetes was induced in male rats by intravenous injection of streptozotocin (50mg/kg). Two weeks after the overt of diabetes, rats were divided into groups each of 10 animals. Groupl received normal saline. Group2 received vitamin E acetate (40mg/kg) every other day by I.P. injection for 4 weeks. Group 3 received sodium selenate (1.89 mg/kg) every day by I.P. injection for 18 days. Group 4 non-diabetic control rats received normal saline. Our results revealed that diabetic rats showed a significant increase in serum glucose, blood MDA levels, plasma levels of triglycerides, total cholesterol and β₂-microglobulin. Treatment of diabetic rats with either vitamin E or sodium selenate produced a significant lowering in serum glucose level. Also, they produced a significant reduction in blood MDA level, plasma triglycerides, total cholesterol and β₂-microglobulin.